Identifikasi Faktor-Faktor Penumpukan Realisasi Anggaran Belanja Di Akhir Tahun (Studi Kasus Pada Balai Penelitian Dan Pengembangan Lingkungan Hidup Dan Kehutanan Manado) - Sudarwati, Nina; Karamoy, Herman; Pontoh, Winston (Universitas Sam Ratulangi, 2017)
Abstract. Implementation of the budget is a very important stage in the realization of government programs that have been organized in the National budget. The implementation sometime found difficulties, including the realization of the budget tends to be low in the early years and accumulated at the end of the year. According to Rusqiayati (2014), ideally the realization of the government's budget follows the